Peran Penting Psikologi Manajemen dalam Meningkatkan Mutu Pendidikan - Runtoni Runtoni (Journal on Education, 2023)
The quality of education is very important and improving the quality of education can apply management psychology in order to improve the quality of education. Educational management development programs need to pay attention to the human aspect, because education management is referred to as an organizational process or system and human improvement (human engineering) in relation to an education system, therefore a reference is needed in making educational management, especially in the psychological aspect. This type of research is descriptive-analytical with a qualitative approach. Based on the research objectives, the method applied is descriptive qualitative. The method was chosen to dig up information in the form of words or descriptions related to natural objects. The results of this study are that there are various intelligences that can be proven through management psychology, namely: a) human intelligence, b) multiple intelligences, and c) emotional intelligence. In addition, educational psychology plays a very important role in investigating the psychological elements of how students learn, namely: first, shaping the personality of educators and learning achievement, second, knowing the situation, third, emotions, fourth, arousing learning motivation.